Desenvolvimento de nano partículas de poli (ácido lático-co-glicólico) para veiculação intravenosa de L-asparaginase - Brito, Anna Emmanuela Medeiros de (2017)
Acute lymphocytic leukemia (ALL) is a type of cancer that compromises the maturation of blood cells of the lymphoblastic lineage, being prevalent in children, but with a good chance of cure due to chemotherapy. The biopharmaceutical L-asparaginase (L- ASNase) is one of the main drugs used in the treatment of this neoplasm, but the immunogenicity derived from the bacterial origin of the enzyme currently produced and the consequent short half-life are challenges to be overcome by the pharmaceutical industry. In this sense, nanobiotechnology is a broad platform for the development of drug delivery aimed at the transport of therapeutic enzymes, besides being able to overcome these problems, it still allows better protein stability with regard to aggregation and denaturation that result in a decrease in enzymatic activity and consequently the pharmacological action. Thus, the objective of this work was to obtain and characterize poly (lactic acid-co-glycolic acid) nanoparticles (PLGA) for L-ASNase encapsulation. The double emulsification method by homturrizing with ultraturrax or cavitation with ultrasound probe was used to obtain the systems, using different times (30 or 60 s) and from two types of PLGA 50:50 with different molecular weights (30-60 KDa e 24-38 KDa) and polyvinyl alcohol (PVA) at concentrations of 0.5, 1, 1.5 and 2%. The size and polydispersity of the nanoparticles were evaluated by dynamic light scattering (DLS). The evaluation of the ASNase encapsulation was performed by quantification of total proteins by the indirect (in the supernatant) and direct method (in the ruptured nanoparticle system). By the nessler method, it was possible to observe that the encapsulated enzyme presented greater activity than the free enzyme. The enzyme release study was performed by dialysis, where < 60% of protein was released in 48 hours. The L-ASNase encapsulation monitoring was performed using native gel electrophoresis and zymogram. Circular dichroism was also used to evaluate the conformational changes of the encapsulated enzyme. From PLGA 30-60 KDa systems were obtained with sizes predominantly between 400 and up to more than 1 μm, with large variation in sizes between them, and for PLGA 24-38 KDa the size range is from 380 nm to 670 nm. Cavitation and higher concentration of PVA resulted in the formation of systems without coalescence. The system made with PLGA 24-38 KDa obtained by cavitation with 1% PVA with homogenization time of 60 s was chosen for ASNase encapsulation and presented encapsulation efficiency by the direct method of 86.67% (± 1.84) and by the method of 95.35% (± 0.06). According to the hemolysis essay, the systems with and without the enzyme were nonhemolytic.